2018
DOI: 10.2196/jmir.9085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Technology-Enhanced Learning Programs for Health Care Professionals: Systematic Review

Abstract: BackgroundTechnology-enhanced learning (TEL) programs are increasingly seen as the way in which education for health care professionals can be transformed, giving access to effective ongoing learning and training even where time or geographical barriers exist. Given the increasing emphasis on this mode of educational support for health care practitioners, it is vital that we can effectively evaluate and measure impact to ensure that TEL programs are effective and fit for purpose. This paper examines the curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…Many published medical e-learning evaluations have low-quality scientific standards [12] and often report their results in a narrative manner [12-14] without following a reporting standard for either qualitative or quantitative evaluation. The majority of e-learning interventions rely on self-designed evaluation designs that are rarely validated.…”
Section: The Alpha and Omega Of E-learning: Evaluationmentioning
confidence: 99%
“…Many published medical e-learning evaluations have low-quality scientific standards [12] and often report their results in a narrative manner [12-14] without following a reporting standard for either qualitative or quantitative evaluation. The majority of e-learning interventions rely on self-designed evaluation designs that are rarely validated.…”
Section: The Alpha and Omega Of E-learning: Evaluationmentioning
confidence: 99%
“…Evaluations of technology used in healthcare education often focus on assessing learner satisfaction, the technology device itself, or pre-test and post-test scores (Harder, 2010;Gough et al, 2015;Pickering and Joynes, 2016;Williams et al, 2016;Nicoll et al, 2018). Williams et al's (2016) study of paramedic students assessed the learners' satisfaction with simulation by utilising the Satisfaction with Simulation Experience Scale.…”
Section: Evaluating the Use Of Technologymentioning
confidence: 99%
“…In addition, it has been suggested that studies evaluating the role of technologies in healthcare education often fail to draw on relevant learning theories or models to justify their use of simulation (Murdoch et al, 2014), multiuser virtual worlds (Liaw et al, 2018) and augmented reality (Zhu et al, 2014). Kirkpatrick's model of evaluation is a popular tool in education (Pickering and Joynes, 2016;Nicoll et al, 2018), and was utilised by five of the studies included in the review (Murdoch et al, 2014;Cook and Ellaway, 2015;Guo et al, 2015;Reeves et al, 2017;Liaw et al, 2018). However, Nicoll et al (2018) identified a lack of standard tools for evaluating technology-enhanced learning in healthcare education and emphasised the need for quality evaluation studies that provide "sufficient detail to support transferability or direct future TEL healthcare education programs' design and implementation".…”
Section: Evaluating the Use Of Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, E-SOLAS was developed and underpinned by theory, with a clear rationale as how the intervention components were developed and/or adapted. The use of a formal evaluation model [12] allowed for a more comprehensive understanding of the effectiveness of E-SOLAS training, including the objective evaluation of PTs behavior during training, which is frequently absent from assessments [22,45,46]. Furthermore, the application of the WHO implementation outcomes using mixed methods enabled comprehensive assessment of the feasibility of implementation of this e-learning training program and required adaptations to increase acceptability [23].…”
Section: Strengths and Limitationsmentioning
confidence: 99%